Leishmania (Mundinia) orientalis n. sp. (Trypanosomatidae), a parasite from Thailand responsible for localised cutaneous leishmaniasis - Narissara Jariyapan (2018)
© 2018 The Author(s). Background: Leishmaniasis is an emerging disease in Thailand with an unknown incidence or prevalence. Although the number of properly characterized and clinically confirmed cases is about 20, it is suspected that this low number masks a potentially high prevalence, with clinical disease typically manifesting itself against an immunocompromised background, but with a substantial number of subclinical or cured cases of infection. To date leishmaniasis in Thailand has been mainly ascribed to two taxa within the recently erected subgenus Mundinia Shaw, Camargo & Teixeira, 2016, Leishmania (Mundinia) martiniquensis Desbois, Pratlong & Dedet, 2014 and a species that has not been formally described prior to this study. Results: A case of simple cutaneous leishmaniasis was diagnosed in a patient from Nan Province, Thailand. Molecular analysis of parasites derived from a biopsy sample revealed this to be a new species of Leishmania Ross, 1908, which has been named as Leishmania (Mundinia) orientalis Bates & Jariyapan n. sp. A formal description is provided, and this new taxon supercedes some isolates from the invalid taxon "Leishmania siamensis". A summary of all known cases of leishmaniasis with a corrected species identification is provided. Conclusions: Three species of parasites are now known to cause leishmaniasis is Thailand, L. martiniquensis and L. orientalis n. sp. in the subgenus Mundinia, which contains the type-species Leishmania enriettii Muniz & Medina, 1948, and a single case of Leishmania infantum Nicolle, 1908. This study now enables epidemiological and other investigations into the biology of these unusual parasites to be conducted. It is recommended that the use of the taxonomically invalid name "L. siamensis" should be discontinued.